2022
DOI: 10.1002/asi.24621
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence changes the way we work: A close look at innovating with chatbots

Abstract: An enhanced understanding of the innovative use of artificial intelligence (AI) is essential for organizations to improve work design and daily business operations. This study's purpose is to offer insights into how AI can transform organizations' work practices through diving deeply into its innovative use in the context of a primary AI tool, a chatbot, and examining the antecedents of innovative use by conceptualizing employee trust as a multidimensional construct and exploring employees' perceived benefits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The ethical concerns related to the use of GPT/ChatGPT, such as ownership of generated content and compliance with copyright laws, are applicable to AI, NLP, and chatbots as a whole (Jarrahi et al, 2022; Jobin et al, 2019). These concerns apply to any situation in which AI and chatbot technology is used to generate content or perform tasks that may have legal or ethical implications (Wang et al, 2022). In terms of ownership of generated content, the issue of who holds the rights to text or other content produced by AI and chatbots is a broader concern that applies to the use of these technologies in various contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethical concerns related to the use of GPT/ChatGPT, such as ownership of generated content and compliance with copyright laws, are applicable to AI, NLP, and chatbots as a whole (Jarrahi et al, 2022; Jobin et al, 2019). These concerns apply to any situation in which AI and chatbot technology is used to generate content or perform tasks that may have legal or ethical implications (Wang et al, 2022). In terms of ownership of generated content, the issue of who holds the rights to text or other content produced by AI and chatbots is a broader concern that applies to the use of these technologies in various contexts.…”
Section: Discussionmentioning
confidence: 99%
“…ChatGPT can support the dissemination and diffusion of new research ideas through the creation of better metadata, indexing, and summaries of research findings (Lund & Wang, 2023). Assuming there is trust and usability among the public, this may support the diffusion of research findings through the translation of research into lay language that can be understood by members of the general public (Wang et al, 2022). ChatGPT can also be used as a sort of recommender system, helping with the identification of relevant research studies based on a user's query.…”
Section: Introducing Chatgptmentioning
confidence: 99%
“…Moreover, the observed mediating role of satisfaction in the relationship between workload and trust in ChatGPT is a notable contribution to the literature. While previous studies have demonstrated a positive correlation between workload reduction by chatbots and trust, as well as between trust and user satisfaction [ 42 - 44 ], the role of satisfaction as a mediator between workload and trust has not been explored. Finally, the positive correlation between the risk-benefit perception of using ChatGPT and trust aligns with the findings of previous studies [ 45 - 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the launch of chatGPT, it has been clear that the platform can boost the creativity and productivity of students, teachers, researchers, content creators, and others. From the perspective of development, it is yet to be observed who will benefit the most from chatGPT, and how it will impact the low-income countries and workers in the Global South [48][49][50]. However, there is no denying that chatGPT is more affordable in comparison to human-like AI assistants such as Google Assistant, Alexa, and Siri as they require google devices, echo dot, and iPhone, whereas chatGPT requires internet access and basic literacy level.…”
Section: Digital Dividementioning
confidence: 99%